Perbanyakan Tanaman Jambu Mete (Anacardium occidentale L.) melalui Jalur Organogenesis - Rossa Yunita; Ika Mariska; Christiani Tumilisar (Jurnal AgroBiogen, 2012)
Vegetativepropagation through in vitro culture has been carried out asa technology that has the potential for obtaining seedling insignificant amounts and relatively faster. This activity can bedone through the multiplication of adventitious shoots andlateral shoots (organogenesis). The goal of this research wasto find the method of cashew micropropagation throughorganogenesis. This study consisted of 4 main activities.They were shoot induction, shoot multiplication, shootelongation, and root induction. The results showed the bestmedium composition for shoot induction was MS + BA 0.7mg/l. The suitable media for shoots multliplication was MS +thidiazuron 0.5 mg/l + zeatin 1 mg/l and for shootselongation was MS + GA 1 mg/l + zeatin + 3 mg/l. The bestmethods for root induction was by submerging in vitroshoots in a solution of IAA 100 mg/l.